PENGEMBANGAN KAWASAN WISATA AGRO DI KECAMATAN NGUNTORONADI KABUPATEN WONOGIRI JAWA TENGAH - Ninuk Purnaningsih; Yeti Lis Purnamadewi (Indonesian Journal of Socio Economics, 2019)
Rural areas have the potential of areas that can be developed based on the condition of natural resources. However, in developing the region, it is necessary to pay attention to the sustainability of being able to meet the welfare of the community. Nguntoronadi District, Wonogiri Regency has the potential of natural resources based on the agricultural sector which can be developed in the development of agro tourism areas. This study uses a quantitative data approach obtained through questionnaires based on interviews and direct observation based on analysis of village independence and supported by qualitative data in the form of in-depth interviews, FGD (Focus Group Discussion) and literature studies. In addition, the SWOT analysis is used as a formulation of tourism development strategies in Nguntoronadi District. The results showed an analysis of the independence of the villages in the four agro tourism development areas in Nguntoronadi Subdistrict included in the Pre Mandiri 4 category with good value categories. This means that potentials that are ready to be developed include infrastructure potential, educational potential, health potential, socio-economic and environmental potential, micro small business potential, and plantation potential. In addition, several strategies that can be implemented in developing agro tourism in Nguntoronadi District include: (1) Designing creative, innovative and economic / commercial value agro-tourism ideas / products based on superior commodities or commodities, (2) Developing agro tourism areas in Nguntoronadi District integrated in the PKLp agro tourism area, and (3) Development and training of HR management of information and technology-based tourism areas (management based on technology and information).Keywords: Village independence; agro tourism development; tourism development strategy